Etnofarmakologi Tumbuhan Familia Rhizophoraceae oleh Masyarakat di Indonesia (Jurnal Bioconcetta, 2017)
Etnofarmakologi is a study that use of plants as medicine by the people who inhabit a particular territory. Some people in Indonesia still use herbs as medicine traditionally, as well as the communities living around the mangrove forests. One of the is Rhizophoraceae, This plant is generally the main constituent of plant mangroves. This study aimed to determine the relative utilization Rhizophoraceae as medicinal plants in the mangrove forest. The results of this research, there are three species of the family Rhozophoraceae were used as a medicinal plant, that are Rhizophora apiculata, Ceriop tagal dan Bruguiera gymnorrizha. Plants are used for cold, treatment in the postpartum period of healing, ulcers and stomach pain. Part of plant that used are the leaves, flowers, fruit and bark. These herbs are processed by boiling to drink and there are mashed to rub.